PERGAULAN MUDA MUDI (Studi Kasus Desa Sukamaju Kecamatan Singingi Hilir Kabupaten Kuantan Singingi) - Ramadani, Amalia Putri; Rosaliza, Mita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to find out how young / young people are interacting and how young people's social supervision is in the village of Sukamaju, downstream singing district. The population in this study is young people based on data from Sukamaju village office in 2017 The population in this study was 150 people with a sample taken of 10 young people using the Nonprobability Sampling group sampling technique. Nonprobability Sampling is a sampling technique that does not provide equal opportunity or opportunity for each element or member of the population to be selected as a sample. Data collection methods are observation, in-depth interviews and documentation. The results of this study indicate that adolescents or young people in the village of Sukamaju have a fairly free relationship most of the teens have made dating patterns that make physical contact such as holding hands, hugging, kissing on the cheek, kissing the lips and even having sexual relations. With social supervision young people in the village like to progress that are still inadequate and the parents' trust in their children being misused by young people in the village of Sukamaju. This means that the lower the vigilance of parents to their children causes behavior deviations in adolescent relationships the greater.Keywords: young people, behavioral deviations, association, social supervision, society.